ENCOURAGING STUDENTS’ MOTIVATION TO WRITE WITH GOOGLE SITE. - Jusriati Jusriati (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This study discussed about students’ motivation in using google site as tool in teaching writing. This study used both quantitative and qualitative method. The instrument consist of observation, questionnaire and interview. After analyzing the findings and discussion in the preceding chapter, it can be concluded that utilizing Google Site as an online learning platform stimulates students' motivation in learning writing. The students demonstrated a significant degree of motivation when learning Descriptive Text through Google Site. They were enthusiastic about learning English and were supportive of using Google Site as an effective online learning medium. To motivate students, it is essential for teachers to employ diverse media, as evidenced by the results of this study, which show that using the Google Site application motivates students to learn English, as demonstrated by the dominant extrinsic motivation among the students.